Pedagogía Cultural: Paradigma crítico-creativo del saber-hacer referido a la educación - López Herrerías, José Ángel (Teoría de la Educación. Revista Interuniversitaria, 2009)
The paradigm of the CULTURAL PEDAGOGYtries to offer an archievement and change the very important perspective into the pedagogical knowledge, as the science of education. We have then to revise the functionalist schedule of the formal, informal and no-formal education. For this, on the one hand, to involve the pedagogical science, concerning to the individual and social, in other model most comprenhensive and easy with the proposal alternatives in the pedagogical action. People musn't learn anything as an individual or social being, although we are willing and able to learn with a gramatical experience in a cultural way. On the other hand, we want to achieve the former purpose, we manage a radical and coherent relation between the educational projection and the global cultural context. The suggestion of learnings, pedagogically projected, is connected with the reading, the interpretation and the change of the cultural environment, as a context of signs, wich builds the whole reality of the world. The psychical development and maturity aren't all learnings of individual being, but they area the references in a constant appeal and inwardness of the whole bio-psycho-social-cultural being, that is an everybody experience, put inside the bio-psychical construction of each person {cultural reality) and put outside the environmental world of experiences and rules {cultural reality